Nuevos paradigmas para la formación de los recursos humanos en bibliotecas y centros de documentación - Hernández Pacheco, Federico (Documentación de las Ciencias de la Información, 2007)
Within the management of the human resources, training is one of the fundamental activities that they influence in the continuous improvement of all the areas that compose to the libraries and documentation centers. The following article presents/displays the tendencies and concepts of the training, as well as the elements that are due to integrate in the design and planning of a program, in which, among other subjects, include modern techniques of education-learning and management of training programs more and more used in public and deprived organizations.